The effect of copper and antimony on the mechanical properties of pewter alloys made by conventional and microwave powder sintering - Mohamed Ariff, Tasnim Firdaus; Gabbitas, Brian Leslie; Zhang, Deliang (2009)
Three different compositions of pewter alloy made using tin, copper and antimony powders were sintered using microwave and conventional sintering. The effect on mechanical properties from green density, sintering method and the weight percentage of copper and antimony added to the tin alloy were examined. Samples were compacted using two different compaction loads (30kN and 40kN) and then sintered at 220°C for both sintering methods. Samples in the conventional furnace were sintered for 120 minutes while samples in the microwave furnace were sintered for 30 minutes. Those samples with a higher green density resulted in higher sintered density, hardness and tensile strength for both sintering methods. Increasing the copper and antimony content resulted in higher hardness and higher tensile strength but lower toughness. Microwave sintering produced samples with improved mechanical properties after a much shorter sintering time compared with those samples which were conventionally sintered.